Averting Educational Crisis: Funding Cuts, Teacher Shortages, and the Dwindling Commitment to Public Education - Derek W. Black (Washington University Law Review, 2017)
Recent data shows that two-thirds of states are funding education at lower levels than in 2008. Some states are 20% or more below levels of just a few years earlier. The effect on schools has been devastating. States are only exacerbating the problem by reducing teachers’ rights and benefits. These attacks, combined with funding decreases, have scared many prospective teachers away from the profession. The net result is an extreme shortage of teachers nationwide. When the school year began in 2015, a large number of public schools opened without enough certified teachers to fill classrooms, relying instead on substitutes and interns on a full-time basis. In other instances, schools stopped offering certain classes. Decades of social science research demonstrate that these funding and teaching policies will have serious academic impacts on students. They will likely widen achievement gaps and impose learning deficits that some students will never overcome. In the face of analogous threats, courts in the past have regularly intervened to protect educational quality and funding. Yet this time around, courts have increasingly refused to intervene and have rarely offered a compelling reason for the refusal. This judicial passivism towards education marks a troubling new trend. It suggests that the constitutional right to education may exist only in theory, and that students are losing the constitutional leverage to demand that states repair the damage that they have caused. Likewise, nothing will prevent states from pursuing similar retractions again in the future. This Article offers a new doctrinal approach to reverse both educational retractions and judicial disengagement. Current trends, however, cannot be reversed without acknowledging the potential limits of judicial intervention during crisis. In particular, a serious crisis incites fear and political expediency, which can prompt legislatures to ignore court orders that purport to remedy the crisis. This disregard is inherently problematic for both education rights and the basic legitimacy of judicial authority, regardless of the subject matter. In this respect, the solution to the devaluation of education rights is also a step toward strengthening judicial authority. In education, courts must begin to incorporate prospective doctrines and rules that reduce the likelihood of judicial standoffs with legislatures. In short, future court orders should seek to avert crises by addressing them before they occur. This Article proposes three specific steps courts can take to achieve this end.
Keywords: education; funding; teachers; judicial intervention; education policy